Implementation of The Excellence Theory to Enhance Reputation of Indonesian National Police - Frizki Yulianti Nurnisya; Suriati Saad; Shuhaida Md Noor (USIM Press, 2024)
Vol. 2 No. 2 (2022) Page(23-49)